Development of an Environment for Virtual Information Retrieval in UPMNET - Hussain, Hanafizan (1997)
In this study, the development of an environment for virtual information retrieval in UPMNET that uses Internet tools such as email, USENET, BITNET, Gopher, WAIS, FTP, Telnet, Archie, Hytelnet, IRe, WWW etc is proposed. The purpose of this project is to gather all these tools to access or retrieve the information at any time. The methodology for this project is based on the concept of hypertext and hypermedia including HTTP, browser, HTML and URL. In this project, Internet tools have been categorised into three groups; online discussion, remote on-line database and real-time discussion. On-line discussion has been used for sharing ideas continuously, for instance using email while remote on-line database can be used for searching information in other various databases. Real-time discussion allows for academicians to have real life conversations as though they are in a 'face to face' situation. Another feature of this project is the development of a prototype of an electronic version for PERTANIKA Journal of Science and Technology. This prototype will consist of information on author, title, year of publishing, abstract of article and email of the author. This will enable academicians to share the ideas and disseminate their knowledge. It also represents one of the steps towards the implementation of an environment for virtual information retrieval in UPMNET. The study concludes with recommendations for further research on enhancing UPMNET applications particularly in the realms of office automation, research and dissemination of scholarly information.